Drug-related celebrity deaths: A cross-sectional study. Issue 1 (December 2016) - Just, Johannes; Bleckwenn, Markus; Schnakenberg, Rieke; Skatulla, Philipp; Weckbecker, Klaus
Abstract Background Celebrities are at risk for premature mortality as well as drug-related death. Despite being a vulnerable patient group, celebrities influence people's health behaviours through biological, psychological and social processes. Therefore, celebrity endorsement of the topic could be one way to challenge the current "opioid endemic". Our aim was to better understand the factors surrounding drug-related celebrity deaths by investigating the incidence as well as substances used between 1970 and 2015 using a cross-sectional study design. Method We searched public databases for drug-related celebrity deaths between 1970 and 2015. They were categorized for sex, profession, age at death, year of death and substances involved. The main outcome measures are descriptive values including number of drug deaths per year and substances involved. Secondary outcome measures are analytical questions to examine whether and which factors influence age at death and year of death (e.g. type of substance use disorder). Results We identified 220 celebrities who died a drug-related death with a clear indication of involved substances between 1970 and 2015. The average age at death was 38.6 years; 75% were male. Most celebrities died between the age of 25 and 40. The number of drug-related deaths increased in the 21st century, with a significant increase in the use of prescription opioids. Deaths involving prescription opioids and heroin were associated with a significantly lower mean age at death compared to deaths where these substances were not involved. Conclusions Compared to the 20th century, the total number of celebrities who died from a drug-related death in the 21st century increased, possibly due to an increased involvement of prescription opioids. Negative effects on individual health decisions of celebrity's followers could be the result.